SELF-EFFICACY, GOAL ORIENTATION DAN SELF REGULATED LEARNING PADA MAHASISWA - Nanda Fitriastuti; Dewi Mustami’ah; Lutfi Arya (Fakultas Psikologi Universitas Hang Tuah, 2021)
Self-regulated learning is an individual's ability to regulate himself in terms of learning independently by involving metacognition, motivation, and behavior so that learning goals are achieved. Self-regulated learning has factors that can influence it, including self-efficacy and goal orientation. This study aimed to determine the relationship between self-efficacy and goal orientation with self-regulated learning. This study used a quantitative approach with a correlational type. Respondents were students of the Faculty of Psychology, Hang Tuah University, Surabaya class of 2019. Respondents totaled 75 students, selected using a saturated sampling technique. This study uses a self-regulated learning scale, a self-efficacy scale, and a goal orientation scale. The results of the study show that self-efficacy and goal orientation together have a significant positive relationship with self-regulated learning with an effective variable contribution of 58.4%.